Mesozoic invertebrate paleontology. Preface - Ricardo Barragán-Manzo; Ana Bertha Villaseñor-Martínez (Revista Mexicana de Ciencias Geológicas)
This special section presents contributions from the Session No. 19 “Mesozoic Invertebrate Paleontology” of the 99th Annual Meeting of the Cordilleran Section of the Geological Society of America, held at the Hotel NH Krystal in Puerto Vallarta, Jalisco, Mexico on April 1-3, 2003.